Implementation of Notary in Relation to Private Debt Agreeements Recorded in Special Register - Dita Rakhma Septiani (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2026)
This research examines the implementation of the principle of prudence by notaries in the registration of private debt agreements in the special register (waarmerking). In Indonesian notarial law, waarmerking is strictly administrative and, pursuant to Article 1875 of the Civil Code (KUHPerdata), does not transform a private deed into an authentic deed. Nevertheless, Article 16 paragraph (1) letter a of the Notary Law (UUJN) explicitly mandates that notaries act honestly, carefully, independently, and impartially in carrying out every professional function. This normative obligation applies not only when drafting authentic deeds, but also when exercising auxiliary administrative authorities such as registration. The study employs a normative juridical method with statutory and doctrinal approaches, drawing on primary and secondary legal sources as well as relevant jurisprudence. The findings demonstrate that failure to apply the principle of prudence in waarmerking generates layered consequences: for the parties, it reduces evidentiary value and creates litigation risks; for the deed, it risks misrepresentation of legal status; and for the notary, it entails civil, administrative, and ethical liability. The conclusion emphasizes that prudential conduct functions as both a normative safeguard and a professional standard, ensuring that administrative acts of registration reinforce, rather than undermine, legal certainty.